Community Satisfaction Analysis Based on Physical Quality of Green Open Space in Takengon (Case Study: Taman Aman Dimot) - Koara, Fakhry Perdana; Marisa, Amy; Nasution, Achmad Delianur (Green Publisher Indonesia, 2023)
The increasing number of human populations causes the density of development that continues to occur. This is done to ensure that the development carried out no longer damages’ nature. One of them is by creating Green Open Space (RTH) or Green Open Space, especially in big cities. In Takengon City, the government wants to make Takengon City a child-friendly city, a healthy city, and a livable city. The purpose of this study is to analyze the level of public satisfaction with Green Open Space in Taman Aman Dimot. The type of research used in this study is descriptive research with quantitative and qualitative approaches. The results of the study, among others, are; (1) Park sociability aims to analyze supporting facilities that support opportunities to socialize with two indicators, namely opportunities to socialize and the environment, (2) comfort is one of the factors for city parks to measure park visitor satisfaction, (3) park visitors, such as the condition of facilities and the number of facilities and cleanliness of the park are the reasons for visitors to be less comfortable, (4) maintenance of park cleanliness is key in the management process park, (5) criteria that become the next category, namely Park Infrastructure, facilities contained in the park such as seating facilities, sports equipment, the condition of facilities and other supporting facilities are very poor, and (6) the criteria for a comfortable park according to visitors in general such as the cleanliness of the park, the amount of vegetation (trees) and complete and well-maintained facilities are the opinions of visitors to give the impression of comfort.